Przekład literacki na cztery ręce, czyli o warsztacie niemieckiego tandemu tłumaczy Ksiąg Jakubowych Olgi Tokarczuk - Anna Majkiewicz (Ksiegarnia Akademicka Publishing, 2021)
Literary Translation in Four Hands – the Workshop of the German Translation Tandem of Olga Tokarczuk’s The Books of Jacob